Safety assessment of a fenugreek dietary fiber-based formulation of capsaicinoids-rich red chili (Capsicum annum) extract (Capsifen®): Acute and sub-chronic studies. (2020) - Joseph, Ashil; NM, Johannah; Kumar, Suresh; S, Syam Das; Maliakel, Balu; IM, Krishnakumar
Abstract: Despite the promising health beneficial effects (thermogenic, lipolytic, hypotriglyceridemic, hypocholesterolemic, anti-inflammatory and anticancer) of capsaicinoids-rich red chili pepper, commonly known as cayenne pepper ( Capsicum annum or Capsicum frutescence ), its consumption at physiologically relevant dosage is always hampered by the pungency and stomach discomforts. The present study examined the safety of a pungency-masked and sustained release food-grade formulation of capsaicinoids-rich red chili pepper extract using fenugreek derived galactomannan soluble dietary fiber (Capsifen®). The safety was assessed by oral acute (300, 2000, 5000 mg/kg b. wt. for 14 days) and subchronic (250, 500 and 1000 mg/kg b. wt.) toxicity studies in Wistar rats. None of the group of animals belonging to both acute and subchronic treatments did produce any adverse events in feeding behavior, urine analysis, and in hematology/biochemical parameters when compared to the control. However, a decrease in body weight was observed among 500 and 1000 mg/kg b. wt. treated groups. The terminal autopsy did not reveal any alterations in relative organ weight except for the high dose treated group, where an increase in liver and kidney weight was observed. Histopathology of all the animals was normal. Thus, the Low-observed-adverse-effect level (LOAEL) of Capsifen was determined for 500 mg/kg b. wt. /day.